Effect of fermented milk with Lactobacillus fermentum on the inflammatory response in mice - Santiago-Lopez, Lourdes (2018)
Currently, the effect of fermented milk on the T-helper 17 response in inflammatory bowel diseases (IBDs) is unknown. The aim of the present study was to evaluate the effect of milks fermented with Lactobacillus fermentum on the Th1/Th17 response in a murine model of mild IBD. Exopolysaccharide (EPS), lactic acid (LA), and total protein (TP) contents and bacterial concentration were determined. Male C57Bl/6 mice intragastrically received either raw (FM) or pasteurized (PFM) fermented milk before and during a dextran sulfate infusion protocol. Blood, spleen, and colon samples were collected at Weeks 6 and 10. IL-6, IL-10, and TNFα were determined in serum, and IL-17, IL-23, and IFNγ were determined in intestinal mucosa and serum. The FM groups did not differ in cell concentration, LA, or TP content (p > 0.05); FM-J28 had the highest EPS content. Spleen weight and colon length did not differ among the FM groups (p > 0.05). In the FM-J20 and PFM-J20 groups, IL-17 and IFNγ decreased, and the IL-10 concentration was enhanced (p < 0.05) at Week 6. IL-6, TNFα, IL-23, and IFNγ did not differ in serum and mucosa (p > 0.05), and IL-17 was lowest in FM-J28 and FM-J20. Therefore, FM appears to potentially play a role in decreasing the Th17 response. However, further studies are needed to elucidate the FM-mediated anti-inflammatory mechanisms in IBD